REPRESENTASI DISKRIMINASI PEREMPUAN DALAM SERIAL TELEVISI AMERIKA SERIKAT (ANALISIS SEMIOTIKA ROLAND BARTHES TERHADAP SERIAL AMERICAN HORROR STORY: CULT (2017) - Angelo Lucky Budiman (MEDIAKOM : Jurnal Ilmu Komunikasi, 2022)
Gender discrimination causes inequality between men and women, which impacting women’s representation in America which has democratic values. This contradicting the equality aspect which causes difference between values held by America and reality that is happening. This research aims to determine the representation of women's discrimination shown by American television series as visual media. This research’s object is Cult, seventh season of American Horror Story series which discusses horrors and fears caused by discrimination. Television series was chosen as research’s object because its power and abiliy to reflect social reality and reach many audiences from various demographics. This research was conducted through collecting, analyzing, and interpreting data process, with documentation and observation methods, and uses Roland Barthes' Semiotics model because of its ability to reach signs that are close to social life and myths. Results showed that representation of Cult’s women character is a person who is limited in social reality, functionally and in role, which includes Marginalization, Subordination, Stereotypes, Violence, and Double Burden as the outcome. Women’s discrimination departs from America’s culture and gender construction which close to patriarchy and subordination. This research’s myth is that women's discrimination and gender inequality prevent them from fully contributing to American life.